2022
DOI: 10.1038/s41467-022-31407-z
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic interactions between the mediodorsal thalamus and prefrontal cortex precede human visual perception

Abstract: The thalamus is much more than a simple sensory relay. High-order thalamic nuclei, such as the mediodorsal thalamus, exert a profound influence over animal cognition. However, given the difficulty of directly recording from the thalamus in humans, next-to-nothing is known about thalamic and thalamocortical contributions to human cognition. To address this, we analysed simultaneously-recorded thalamic iEEG and whole-head MEG in six patients (plus MEG recordings from twelve healthy controls) as they completed a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…Empirically, intracranial recordings in patients revealed a decrease in NC alpha, which preceded fast gamma oscillations in MTL networks during memory encoding ( Griffiths et al, 2019 ). This complements former evidence that reduced EEG alpha power facilitated information processes when preceding relevant sensory input (e.g., Romei et al, 2008 ; Busch et al, 2009 ; see VanRullen, 2016 , for a review; Griffiths et al, 2022 ). An inverse relation between local field alpha desynchronization and neural firing rates in sensory cortical regions has been found in monkeys ( Haegens et al, 2011 ), and the alpha rhythm has been shown to exert top-down influences in the visual cortex of macaques ( Bastos et al, 2015 ; Richter et al, 2017 ).…”
Section: Neural Rhythms – Temporal Dynamics Of Neural Computationsupporting
confidence: 84%
“…Empirically, intracranial recordings in patients revealed a decrease in NC alpha, which preceded fast gamma oscillations in MTL networks during memory encoding ( Griffiths et al, 2019 ). This complements former evidence that reduced EEG alpha power facilitated information processes when preceding relevant sensory input (e.g., Romei et al, 2008 ; Busch et al, 2009 ; see VanRullen, 2016 , for a review; Griffiths et al, 2022 ). An inverse relation between local field alpha desynchronization and neural firing rates in sensory cortical regions has been found in monkeys ( Haegens et al, 2011 ), and the alpha rhythm has been shown to exert top-down influences in the visual cortex of macaques ( Bastos et al, 2015 ; Richter et al, 2017 ).…”
Section: Neural Rhythms – Temporal Dynamics Of Neural Computationsupporting
confidence: 84%
“…In this study, we theorize that P1 and P2 were triggered by the sensory input, which suggests the existence of direct pathways that bypass intermediate hierarchical levels. One possible route is the thalamocortical pathways, which converge with corticocortical pathways to enable higher auditory and visual perception 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The second prediction of our model is that a stable temporal code emerges from approximately synchronous oscillations in the consecutive network layers. Recent work using concurrent iEEG and MEG recordings has suggested that interactions between alpha oscillations in prefrontal cortex and mediodorsal thalamus mediate visual performance [41]. In light of the literature on travelling alpha waves [6, 4, 5, 9, 27, 65, 124] this begs the question of whether neuronal processing along the visual hierarchy is controlled by one driving force as suggested by our simulations, e.g.…”
Section: Discussionmentioning
confidence: 65%